Propriedades físicas, fracionamento da matéria orgânica do solo e produtividade da soja em sucessão a plantas de cobertura no inverno - Anschau, Katiely Aline (2018)
The agricultural production systems have as fundamental component the soil, being necessary the use of practices that promote the sustainability of the system, providing the conservation of the natural resources without adversely affecting the production of the agricultural areas. The objective of this study was to evaluate the biomass productivity of winter cover crops in monoculture and intercropping, and their effects on soil physical properties (macroporosity (Ma), microporosity (Mi), total porosity (Pt), soil density soil (Ds), soil penetration resistance (Rp) and stability of aggregates) after the cultivation of cover crops and soybean in succession; (AF), humic acids (HH) and humin (HU)) after covering plants in different layers and; to evaluate soybean yield in succession to cover crops grown in the winter. The experimental design was a randomized complete block design with six treatments and four replications. The treatments used were: black oat, black oat + forage turnip, forage turnip, forage pea, black oat + forage pea and control (fallow); being the soybeans later sown on the straw of these hedge plants. Soil samples were collected at 0 - 0.10; 0.10 - 0.20 and 0.20 - 0.30 and 0.30 - 0.40 m and 0.0 - 0.20 - 0.20 - 0.40 m. The use of a consortium between forage turnip + oats and forage pea + oats promoted a greater contribution of biomass to the soil, promoting improvements in Ma and Rp. Coverage plants, due to the short time of implantation, did not provide changes in the stability of aggregates and stable fractions of MOS. For cultivation of soybeans cultivated after the cover crops there was an increase in productivity and improvement in Ma, Ds, Rp and DMP, showing that the use of green fertilizers brings benefits to the cultivation system.